Internalisasi Makna Kata “Di Bumi Seperti Di Surga” Dalam Matius 6:10c Dan Praktik Konkritnya - Rouw, Julian Frank (Integritas: Jurnal Teologi, 2019)
This article discusses the internalization of the meaning of the word "on earth as in heaven" in Matthew 6: 10c and its concrete practices. The author conducted a study of the text of Matthew 6: 10c and elaborated it with various relevant library sources. From the analysis of the text of Matthew 6: 10c, the church has a goal of bringing the message of Christ and the love of God, making it interesting and understandable, for all groups of people, especially those who are powerless and cannot voice their interests. The church also needs to be involved in the development of a society that is in accordance with God's will, so that it can bring shalom in the midst of society. Therefore, the church needs to be actively involved in contributing to building the community.